Serotype-specific serum immunoglobulin G at 18 months of age following one or two doses of a primary series of 10-valent or 13-valent pneumococcal conjugate vaccine and a booster dose at nine months of age: a randomized controlled study - Alane Izu; Eleanora Aml Mutsaerts; Courtney Olwagen; Lisa Jose; Anthonet Koen; Amit J Nana; Clare L. Cutland; Shabir A. Madhi (Expert Review of Vaccines)
Background Due to high costs of pneumococcal conjugate vaccines (PCV), transitioning from a two (2 + 1) to a single dose (1 + 1) primary series with a booster should be considered. This study evaluated the immune response at 18 months of age following a 1 + 1 compared to a 2 + 1 schedule of 10-valent (PCV10) and 13-valent (PCV13) vaccines.Research design and methods A single-center, open-label, randomized trial conducted in Soweto, South Africa, evaluated the immunogenicity of differing dosing schedule for PCV10 and PCV13. Six hundred children were randomly assigned to six study arms (1:1:1:1:1:1). Non-inferiority was concluded when the lower limit of the 96% confidence interval of the ratio of geometric mean concentrations (GMCs) of the 1 + 1 and 2 + 1 schedules was >0.5 for at least 10 and eight of the PCV13 and PCV10 serotypes, respectively.Results GMCs in children who received the PCV13_6w + 1 and PCV13_14w + 1 schedule were non-inferior for 11 and 10 of the PCV13 serotypes, respectively, compared with the PCV13_2 + 1 arm. For PCV10, GMCs for both 1 + 1 schedules were non-inferior to a 2 + 1 schedule for nine of the PCV10 serotypes.Conclusion Transitioning to a 1 + 1 schedule should be considered for early immunization programs.Clinical trial registration www.clinicaltrials.gov identifier is NCT02943902.